Whole blood based point-of-care assay for the detection of anti-pertussis toxin IgG antibodies - Knuutila Aapo; Rautanen Carita; Barkoff Alex-Mikael; Mertsola Jussi; He Qiushui (ELSEVIER, 2022)
Current serological diagnosis of pertussis is usually done by ELISA to determine serum specific anti-pertussis toxin (PT) IgG antibodies. However, the ELISAs are often central-laboratory based, require trained staff, and have long turnaround times. A rapid point-of-care (POC) assay for pertussis serology would aid in both diagnosis and surveillance of the disease. In this study, a quantitative lateral flow assay (LFA) with fluorescent Eu-nanoparticle reporters was used for the detection of anti-PT antibodies from whole blood. The assay was eval-uated by testing overall 141 samples including 25 before and 116 one month after acellular pertussis booster vaccination. LFA results were compared to those obtained with standardized anti-PT IgG ELISAs with paired serum samples. Correlation between the assays was high (Pearson R = 0.832), and the achieved analytical sensitivity of the LFA was 29 IU/mL, which would be sufficient for clinically relevant cutoffs for determining recent infections. The paired samples, collected pre-and post-booster, demonstrated a significant increase in anti-PT IgG antibodies similar to that detected by ELISA. The developed LFA opens up several alternatives for a suitable POC test also in middle-and low-income countries.